2013
DOI: 10.1063/1.4832239
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and magnetic properties of magnetic fluids consisting of shifted dipole particles under the influence of an external magnetic field

Abstract: Articles you may be interested inTheory of magnetic fluid heating with an alternating magnetic field with temperature dependent materials properties for self-regulated heating J. Appl. Phys. 105, 07B324 (2009) We investigate the structure of a recently proposed magnetic fluid consisting of shifted dipolar (SD) particles in an externally applied magnetic field via computer simulations. For standard dipolar fluids the applied magnetic field usually enhances the dipole-dipole correlations and facilitates chain f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 85 publications
1
19
0
Order By: Relevance
“…Our results can be verified for colloidal Janus parti-cles which a strong dipole moment along their symmetry axis. At vanishing self-propulsion these particles have been considered quite a lot in the context of ferrogels and ferrofluids [17][18][19][20][21]52]. Dipolar self-propelled particles have been prepared recently by Baraban and coworkers [53,54] and aggregation into clusters has indeed been observed [55].…”
Section: Introductionmentioning
confidence: 99%
“…Our results can be verified for colloidal Janus parti-cles which a strong dipole moment along their symmetry axis. At vanishing self-propulsion these particles have been considered quite a lot in the context of ferrogels and ferrofluids [17][18][19][20][21]52]. Dipolar self-propelled particles have been prepared recently by Baraban and coworkers [53,54] and aggregation into clusters has indeed been observed [55].…”
Section: Introductionmentioning
confidence: 99%
“…An important example for the former are magnetic dipole moments which enable to actuate and control the swimming path by an external magnetic field [13][14][15][16][17][18][19][20][21]. In the absence of swimming, the structure of two-dimensional [22,23] and three-dimensional [24,25] dipole clusters has been explored recently, but the impact of activity on a swimmer cluster has been rarely studied [19,26]. Recent simulation studies [27,28] have revealed that the mean cluster size crucially depends on the strength of the selfpropulsion speed.…”
mentioning
confidence: 99%
“…This has important consequences for the interactions between swimmers and give rise to qualitatively different fission and fusion scenarios which we classify for small particle clusters. In detail, we study the spontaneous fission processes for two chosen types of clusters, linear chains and rings, representing the ground state of magnetic dipoles [22,25]. While linear chains remain stable for pullers and neutral swimmers they are split in the case of pushers.…”
mentioning
confidence: 99%
“…in Refs. [37][38][39][40]. Once a configuration of magnetic particles is obtained, in the second step, the desired sample shape is cut from the ferrofluid.…”
Section: Modelmentioning
confidence: 99%
“…The analysis is performed in analogy to Refs. [40,41]. Two magnetic particles are taken to be part of the same cluster if their distance is smaller 3.…”
Section: Influence Of the Microstructure On The Deformationmentioning
confidence: 99%